A panel vector autoregressive analysis of Cambodian commercial banks’ loans - Hor, Bunthe; Lim, Siphat (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the dynamic relationship between the components of the CAMELS framework and the loan growth of commercial banks in Cambodia using a Panel Vector Autoregressive (PVAR) model. Regression results reveal that asset quality, management quality, efficiency, and liquidity significantly influence loan growth. Specifically, non-performing loans (NPLs) and return on assets (ROA) have a negative effect, suggesting that poor asset quality and high profitability are associated with more conservative lending behavior. In contrast, management quality and liquidity positively impact loan growth, indicating that operational investment and strong liquidity support credit expansion. Forecast Error Variance Decomposition (FEVD) shows that the influence of internal bank factors increases over time, with capital adequacy and earnings emerging as dominant long-run drivers of loan dynamics, followed by management quality and liquidity. Impulse Response Functions (IRFs) further confirm the negative impact of capital adequacy and ROA, and the positive but weaker responses to management quality and liquidity. Macroeconomic analysis highlights that real GDP growth significantly stimulates loan growth, while inflation has no meaningful effect. Overall, the findings underscore the importance of both internal bank performance and macroeconomic conditions in shaping lending behavior, offering valuable insights for regulators and financial institutions aiming to foster sustainable credit growth.